2016
DOI: 10.1016/j.ijproman.2016.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Balancing contradictory temporality during the unfold of innovation streams

Abstract: International audienceThis article focuses on individuals working on innovation developments during the unfolding of innovation streams. Innovation streams include both exploitation-and exploration-oriented projects. Those projects imply different temporalities and can be conducted at different paces. This research examines how different temporalities within a single innovation stream are managed first at the level of projects and then among projects. We collected data on an innovation stream in the semiconduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 71 publications
1
6
0
Order By: Relevance
“…Time-based structures include, for example, schedules and deadlines (Grandori 1997, Hassard 1991. These structures specify timeframes characterized by clear start dates, milestones, and end dates for the project (Janowicz-Panjaitan et al 2009, Simon andTellier 2016). Each project organization performs different tasks at a specific point in time during the project, but each organization also pursues different interests, thus making the interorganizational project network prone to a misalignment between organizations' timeframes and the project's timeframe.…”
Section: Temporality In Projectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Time-based structures include, for example, schedules and deadlines (Grandori 1997, Hassard 1991. These structures specify timeframes characterized by clear start dates, milestones, and end dates for the project (Janowicz-Panjaitan et al 2009, Simon andTellier 2016). Each project organization performs different tasks at a specific point in time during the project, but each organization also pursues different interests, thus making the interorganizational project network prone to a misalignment between organizations' timeframes and the project's timeframe.…”
Section: Temporality In Projectsmentioning
confidence: 99%
“…Our study extends current research that thus far has suggested that the quality of cross-phase transitions primarily depends on "transition rituals" conducted among project members (Van den Ende and Van Marrewijk 2014). Furthermore, the misalignment between organizations' timeframes and the project's timeframe is a cause of project delays (Simon and Tellier 2016). For example, the completion date for the foundations contractor is much before the project's completion date, but these differences typically develop different temporal notions between organizations (e.g., one-week delays for the foundations contractor is not much, but such a delay compromises the delivery of the project on time).…”
Section: Theoretical Implications About Inter-temporal Aspects In Coomentioning
confidence: 99%
“…Clockspeed is best studied within the context of innovation projects among individuals because, at this level, the dynamics and interactions of multiple clockspeeds are most apparent and influential [38].…”
Section: B Clockspeedmentioning
confidence: 99%
“…However, some authors even argue that conventional time management approaches fall short in comprehending team processes based on a linear clock-time perspective [9]. Notably, the innovation process, from ideation to implementation, is characterised by temporal complexity involving multiple rhythms, speeds, and experiences [38]. Thus, planning, for example, done through scheduling and time management, is routinely reported as a significant source of teamwork-related problems [45].…”
Section: Hypothesis Development and Contextualisationmentioning
confidence: 99%
“…More recently, research on contractual governance distinguishes between the control and coordination functions of formal contracts (Grandori & Furlotti, 2019; Lumineau, 2017) as a means to better explain its use in managing interorganizational relationships. For example, formal contracts frequently feature schedules with associated milestones and deadlines (Grandori, 1997; Simon & Tellier, 2016) that capture the time‐based structures necessary to fulfill coordination needs over time (Humphrey et al, 2004; Van de Ven et al, 1976). When milestones are not achieved and/or deadlines are not met, the perceived feasibility of the project generally decreases, as attaining contractually agreed‐on performance will become increasingly more difficult.…”
Section: Project Setbacks and Governance Adjustment Interplaymentioning
confidence: 99%